2012
DOI: 10.1136/annrheumdis-2012-201958
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-mediated, enhanced production of profibrotic TIMP-1 in monocytes from patients with systemic sclerosis: role of serum factors

Abstract: ObjectivesTo investigate whether monocytes contribute to matrix deposition in systemic sclerosis (SSc) by production of tissue-inhibitor of metalloproteinase-1 (TIMP-1).MethodsMatrix metalloproteinase-1 (MMP-1) and TIMP-1 expression and secretion were measured by qRT-PCR and ELISA in circulating monocytes from patients with SSc, patients with rheumatoid arthritis (RA) and healthy controls (HC) and in healthy monocytes cultured in the presence of SSc or HC serum samples. Production of TIMP-1 was determined in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 36 publications
(35 reference statements)
2
56
0
1
Order By: Relevance
“…HC monocytes were pre-treated with human immunoglobulin G (IgG) for 1 h prior to HC or SSc sera stimulation (IgG block) and HC or SSc sera were incubated with RNA/DNA endonuclease (benzonase) prior to sera stimulation or interleukin-1 receptors-associated kinase 4 (IRAK4 − /− ) monocytes were treated with HC and SSc sera and tissue-inhibitor of metalloproteinase-1(TIMP-1) secretion was measured by ELISA. The data show that RNA and IgG receptors play a role in induction of profibrotic TIMP-1 and that IRAK4 is critical in this process (38). *** Significantly different analysis of variance (ANOVA).…”
Section: Resultsmentioning
confidence: 97%
“…HC monocytes were pre-treated with human immunoglobulin G (IgG) for 1 h prior to HC or SSc sera stimulation (IgG block) and HC or SSc sera were incubated with RNA/DNA endonuclease (benzonase) prior to sera stimulation or interleukin-1 receptors-associated kinase 4 (IRAK4 − /− ) monocytes were treated with HC and SSc sera and tissue-inhibitor of metalloproteinase-1(TIMP-1) secretion was measured by ELISA. The data show that RNA and IgG receptors play a role in induction of profibrotic TIMP-1 and that IRAK4 is critical in this process (38). *** Significantly different analysis of variance (ANOVA).…”
Section: Resultsmentioning
confidence: 97%
“…TIMP-1 production has been described in circulating monocytes of SSc compared with RA patients and controls. When SSc and control monocytes were stimulated with TLR8 agonist, TIMP-1 production dramatically elevated, underlining the role of TLR signaling in ECM remodeling [136].…”
Section: Systemic Sclerosismentioning
confidence: 97%
“…Agarwal et al demonstrated that SSc fibroblasts upregulated TLR3 in response to interferon-α and that this results in enhanced production of IL-6 and monocyte chemoattractant protein-1 (MCP-1) [14], ultimately leading to enhanced recruitment of monocytes in the tissue. We have previously found that stimulation of TLR8 with single-stranded RNA in monocytes leads to increased TIMP-1 secretion [38] (Fig. 2).…”
Section: Intracellular Tlrsmentioning
confidence: 75%
“…2). Further to this, using a patient with a genetic lesion in IRAK4, we could show that this was both IRAK4 and NF-κB-dependant through incubation of the patient's serum with benzonase, an enzyme that facilitates the cleavage of RNA, which leads to diminished induction of TIMP-1 [38]. It is suggested that the RNA species in the SSc patient's serum is complexed with autoantibodies and that this is stimulating the monocytes to produce TIMP-1.…”
Section: Intracellular Tlrsmentioning
confidence: 95%